2008
DOI: 10.1007/s10719-007-9096-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determination of a non-sulfated glycosaminoglycan-like polysaccharide from melanin-free ink of the squid Ommastrephes bartrami by negative-ion electrospray tandem mass spectrometry and NMR spectroscopy

Abstract: A non-sulfated polysaccharide was isolated from the ink sac of squid Ommastrephes bartrami after removal of the melanin granules. The carbohydrate sequence of this polysaccharide was assigned by negative-ion electrospray tandem mass spectrometry with collision-induced dissociation of the oligosaccharide fractions produced by partial acid hydrolysis of the polysaccharide. The structural determination was completed by NMR for assignment of anomeric configuration and confirmation of linkage information and it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…SIP was prepared as previously reported (Chen et al, 2008). Briefly, after squid ink of O. bartrami was acidified to pH 4.0-5.0 with 0.1 M HCl and the solution stood for 24 h at 4°C to precipitate melanin, melanin was removed by centrifugation at 5000 × g for 1 h. Then melanin-free ink was digested with 2 volumes of 1% (w/v) papain in Tris-HCl buffer (50 mM, pH 6.8) containing 5 mM Cys and 5 mM ethylenediaminetetraacetic acid (EDTA) at 60°C for 24 h. Digestion was repeated twice to ensure the cleavage of the protein/peptide moiety.…”
Section: Preparation Of Sipmentioning
confidence: 99%
See 2 more Smart Citations
“…SIP was prepared as previously reported (Chen et al, 2008). Briefly, after squid ink of O. bartrami was acidified to pH 4.0-5.0 with 0.1 M HCl and the solution stood for 24 h at 4°C to precipitate melanin, melanin was removed by centrifugation at 5000 × g for 1 h. Then melanin-free ink was digested with 2 volumes of 1% (w/v) papain in Tris-HCl buffer (50 mM, pH 6.8) containing 5 mM Cys and 5 mM ethylenediaminetetraacetic acid (EDTA) at 60°C for 24 h. Digestion was repeated twice to ensure the cleavage of the protein/peptide moiety.…”
Section: Preparation Of Sipmentioning
confidence: 99%
“…NMR analysis was performed as previously reported (Chen et al, 2008). Briefly, SIP (20 mg) and FTSC-SIP (20 mg) were coevaporated with D2O (99.8%) twice by lyophilization before final dissolution in 500 µL high-quality D2O (99.96%), containing 0.1 mL lacetone.…”
Section: H Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…SIP is a type of glycosaminoglycon with a unique structure Fig. 1) (11,12) and it has been discovered that the bioactive polysaccharides could increase antioxidant capabilities of some tissues including the liver, heart, lungs, and kidneys of model animals exposed to CP (13), which implies that SIP protects normal tissues of model animals from damage induced by the chemotherapeutic drug. Especially, our latest preliminary fi ndings revealed intervention of SIP on CP-induced spermatogenetic damage in mice, the investigated parameters including sperm density, survival rate, abnormality rate, as well as superoxide dismutase activity in testis indicated that SIP could protect the testes from chemotherapeutic damage caused by CP (14,15) and that the marine polysaccharides could be potentially developed as a cytoprotector.…”
Section: Introductionmentioning
confidence: 99%
“…The squid ink has been reported to have anti-radiation activity, antitumor activity, immunomodulatory activity, procoagulant function and so on (Takaya 2000). Several bioactive molecules, including a glycosaminoglycan like polysaccharides (Chen et al 2008), a tyrosinase (Naraoka et al 2003) and an angiotensin-converting enzyme inhibitor (Kim et al 2003) have been identified from squid ink. Among them, the melanin has attracted most research interests.…”
Section: Introductionmentioning
confidence: 99%